Optical response of the Cu2S2 diamond core in Cu2II(NGuaS)2Cl2. Issue 24 (30th June 2016) - Witte, Matthias; Grimm‐Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Gero Schmidt, Wolf; Herres‐Pawlis, Sonja
Abstract : Density functional theory (DFT) and time‐dependent DFT calculations are presented for the dicopper thiolate complex Cu2 (NGuaS)2 Cl2 [NGuaS=2‐(1, 1, 3, 3‐tetramethylguanidino) benzenethiolate] with a special focus on the bonding mechanism of the Cu2 S2 Cl2 core and the spectroscopic response. This complex is relevant for the understanding of dicopper redox centers, for example, the CuA center. Its UV/Vis absorption is theoretically studied and found to be similar to other structural CuA models. The spectrum can be roughly divided in the known regions of metal d‐d absorptions and metal to ligand charge transfer regions. Nevertheless the chloride ions play an important role as electron donors, with the thiolate groups as electron acceptors. The bonding mechanism is dissected by means of charge decomposition analysis which reveals the large covalency of the Cu2 S2 diamond core mediated between Cu d z 2 and S‐S π and π* orbitals forming Cu‐S σ bonds. Measured resonant Raman spectra are shown for 360‐ and 720‐nm excitation wavelength and interpreted using the calculated vibrational eigenmodes and frequencies. The calculations help to rationalize the varying resonant behavior at different optical excitations. Especially the phenylene rings are only resonant for 720 nm.© 2016 Wiley Periodicals, Inc . Abstract : The structural CuA model complex Cu 2 II (NGuaS)2 Cl2 is analyzed using density functional theory. We discuss the molecular orbitals and their relation to other CuA model complexes. Another focus is set on the optical response in UV/Vis spectroscopy and Raman excitations. For comparison, resonant Raman spectra are determined for two excitation wavelengths and analyzed. The experimental spectra are in good agreement with the theoretical predictions and reveal striking similarities with other CuA model complexes.